THE STATISTICAL SIMULATION OF 4-D SEISMIC NOISE FOR FREQUENCY CHARACTERISTICS OF GEOLOGY ENVIRONMENT DETERMINATION - Vyzhva, Z. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The problem of random fields in 4-D space (homogeneous in time as well as homogeneous isotropic in the 3-D space ) statistical simulation has been considered for the introducing into seismic research into frequency characteristics of geology environment. Statistical model of such random fields and numerical simulation algorithm have been developed on the basis of modified Kotelnikov-Shennon interpolation sums for generating of adequate realizations seismic noise.